Biodegradation, efficacy, leachability and strength properties of organotin(IV)-treated hevea brasiliensis, alstonia scholaris and Macaranga triloba wood - Md. Masudur, Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Organotin compounds have been known to possess biological activities and had been used as wood preservatives. Safety and environmental issues limit the use of tributyltin oxide (TBTO) and tributyltin naphthenate (TBTN) wood preservatives to aboveground and industrial applications only. Interest in monosubstituted and disubstituted organotin(IV) compounds is increasing due to their interesting structural features and biocidal properties. The specific objectives of this study were to determine the efficacy of newly synthesized monosubstituted and disubstituted organotin(IV) compounds against wood decay fungi, microdistribution of tin in treated wood cells, enzymes involved in wood biodegradation, and mechanical properties of organotin(IV)-treated woods. Three non-durable tropical wood species namely Alstonia scholaris (pulai), Macaranga triloba (mahang) and Hevea brasiliensis (rubberwood) were chemically treated with two monosubstituted and three disubstituted newly synthesized organotin(IV) complexes using full-cell treatment method. Ten 19 mm x 19 mm x 19 mm sized wood cubes of each species were treated with three levels of concentration (0.1, 0.5 and 1%) of monomethyltin(IV) (MMT) and monophenyltin(IV) (MPT) of the monosubstituted organotin(IV), and dimethyltin(IV) (DMT), diphenyltin(IV) (DPT) and dibutyltin(IV) (DBT) of the disubstituted organotin(IV). Chemical retentions were determined following treatment and the threshold value was determined based on the soil block test results. Chemical bonding in wood cells and microdistribution of organotin(IV) were determined using Fourier transform infrared (FTIR) spectroscopy and scanning electron microscope-energy dispersive X-ray (SEM-EDX) analyses, respectively. Enzyme bioassays were carried out to determine the lignolytic enzyme activities of fungi involved in wood biodegradation. Results showed that all the selected woods are treatable with the newly synthesized organotin(IV) complexes with retention at iv 10.59 kg m-3 was achieved with A. scholaris which was treated with 1% DMT. FTIR spectra and SEM-EDX analyses revealed that organotin(IV) complexes bind with wood and tin was present in fibre cell wall, respectively suggesting that the organotin(IV) complexes are capable of penetrating the cell wall. Leaching test results showed no tin was release after 270 hours. The strength properties were not affected following organotin(IV) complexes except for samples treated with DMT. Enzyme bioassays indicated that MnP was most likely to be the predominating enzymes causing lignin degradation in A. scholaris, M. triloba and H. brasiliensis wood cubes and enzymes activities were reduced in treated wood. Results showed that the best protection against decay fungi was provided by dibutyltin(IV) complex followed by diphenyltin(IV), dimethyltin(IV), monophenyltin(IV) and monomethyltin(IV) complexes. This study showed that the newly synthesized organotin(IV) complexes are effective against T. versicolor and G. trabeum and disubstituted organotin(IV) provide better protection than monosubstituted organotin(IV) to A. scholaris, M. triloba and H. brasiliensis. However further studies such as treating a wide range of wood species, exposing to other wood decay fungi and field tests are necessary to evaluate the true potential of these newly synthesized organotin(IV) complexes.